Online or Face-to-Face, That is the Question: Difference in Learning Experiences for Teachers Receiving Technology Professional Development Using Two Different Delivery Methods - Williams, Kathy R. (My University, 2007)
The purpose of this action research study was to gain information regarding the effects, if any, of delivery method on learning outcomes for teachers receiving instruction on advanced PowerPoint skills delivered using two different delivery methods but with the same follow up. In addition, the study sought to gain information on the effect of delivery method and/or one-on-one follow up support as it related to teacher confidence for integrating new technology skills into instruction. As outlined in the action research proposal, this qualitative study included instruction delivered to ten elementary teachers over a three and a half week time span using the whole group all at once format and the computer based standalone format. Following instruction, each participant created and taught two lessons using the advanced PowerPoint skills presented through the technology professional development instruction. As described in the article manuscript, data was gathered before, during, and after the intervention using pre- and postintervention teacher belief surveys, pre-, mid-, and post-intervention PowerPoint skills surveys, assistance request frequency charts, one-on-one follow up sessions, formal observations, teacher questionnaires post-intervention, and a focus group discussion.. Results of the study indicated that teachers were positive about their delivery method and the learning that occurred during the study. Positive gains were seen in the areas of teacher confidence for integrating new skills into instruction and in teacher beliefs about the role of technology and technology professional development. The results of this study were communicated to the learning community through a formal discussion during monthly committee meetings. Feedback supported investigating alternate methods of delivering technology professional development in an effort to increase teacher confidence for integrating technology into their curriculum.
Keywords: PowerPoint skills; integrating; instruction